The neuroprotective effect of Chinese herbal medicine for cerebral ischemia reperfusion injury through regulating mitophagy - Chen, Yanling; Zhang, Yanan; Wu, Qin; Chen, Jing; Deng, Yihui (Frontiers in Pharmacology, 2024)
The incidence of ischemic stroke has been increasing annually with an unfavorable prognosis.Cerebral ischemia reperfusion injury can exacerbate nerve damage. Effective mitochondrial quality control including mitochondrial fission, fusion and autophagy, is crucial for maintaining cellular homeostasis. Several studies have revealed the critical role of mitophagy in Cerebral ischemia reperfusion injury. Cerebral ischemia and hypoxia induce mitophagy, and mitophagy exhibits positive and negative effects in cerebral ischemia/reperfusion injury. Studies have shown that Chinese herbal medicine can alleviate Cerebral ischemia reperfusion injury and serve as a neuroprotective agent by inhibiting or promoting mitophagy-mediated pathways. This review focuses on the mitochondrial dynamics and mitophagy-related pathways, as well as the role of mitophagy in ischemia-reperfusion injury. Additionally, it discusses the therapeutic potential and benefits of Chinese herbal monomers and decoctions in the treatment of ischemic stroke.